RELEVANSI EVANGELIUM GAUDIUM DALAM PELAYANAN PASTORAL SEKOLAH KATOLIK: REFLEKSI TENTANG PERAN SEKOLAH DALAM MEWARTAKAN INJIL - Mukin, Yohanes Hego; Bala, Gerardis Mayela Barek; Raring, Elisabeth Wesan; Lamarobek, Noviana Boleng; Kwen, Krisantus Minggu (Jurnal Masalah Pastoral, 2025)
School pastoral care is an important part of Catholic education to increase the development of children's faith as adults and able to implement it in daily life. However, there are still problems that occur in the implementation of school pastoral in preaching the Gospel in every school institution. The purpose of this research is the Relationship of Evangelium Gaudium with the Pastoral of Catholic Schools: Reflections on the Role of Schools in Proclaiming the Gospel. The research method used is a qualitative research type with a literature review approach. The results found were; First, the EG-School Symbiotic Relationship; EG as a theological foundation, schools as an operational field; Second, the key problem; Academic elitism, pastoral fragmentation, weak response to the times; Third, Solutions; Integrative model based on 3 pillars (inculturative curriculum, encounter community, partnership);  Fourth, School Identity; Prophetic space: agents of change, laboratories of values, communities of hope; Fifth, Future Challenges; Reform of inclusive policies and teacher-missionary formation. Thus the importance of the application of Evangelium Gaudium in Catholic education through school pastoral care as a deeper and more concrete proclamation of the Gospel for students.